The employment policy and vocational activity support system for people with intellectual disabilities in Poland: emancipation policy or apparent actions? - Woynarowska, Agnieszka (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
This article presents problematics related to social policy and the system supporting the vocational activity of persons with intellectual disabilities in Poland. Analyses aimed at finding an answer to the question posed in the title are based on the results of a research project entitled Employment and disability. An analysis of the vocational experience of people with intellectual disabilities in Poland, which aimed at an exploration of the policy of the employment of persons with disabilities, practices in the area of employment services, and a reconstruction of the experience of subjects involved in the work situation: job coaches, persons with intellectual disabilities, and coordinators of employment projects. The methodological framework of the project was provided by the grounded theory set in social constructivism as presented in Charmaz’s works. The research material was collected in 25 workplaces employing persons with disabilities in various parts of Poland, mainly by means of in-depth interviews, observation, and field notes. The paper presents only a small fragment of the research results. The analyses focus on the presentation of the assumptions, goals, and trends of the employment policy, ways of functioning of the system of support of the vocational activity of persons with intellectual disabilities, and the confrontation of these systemic assumptions with the experience of persons involved in the implementation of this employment policy in the Polish reality. The article is therefore a critical analysis of the current policy of the employment of persons with intellectual disabilities, unmasking the existing paradoxes and apparent actions in the system of vocational support and the labour market